The Politics of Pine Tree Disease: Interspecies Politics in the Inter-Korean Borderlands - Kim, Junsoo (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
This study explores the politics of interspecies relationships in the inter-Korean borderlands. Pine trees (Pinus) are regarded as significant national symbols in both North and South Korea, making them a relevant topic in interKorean politics. As a result, diseases affecting pine trees have come to be viewed as an enemy of the state for the two Koreas. The spread of pine tree disease from the southern regions of South Korea to the northern parts of the Korean Peninsula has prompted both states to implement biosecurity measures. This research demonstrates how these biosecurity measures are enforced despite restrictions on human access to the Demilitarized Zone (DMZ) between the two Koreas. To better understand this, I propose a framework of more-than-human territoriality, which analyzes how biosecurity measures shape and are shaped by interspecies interactions, highlighting the geopolitical implications of these dynamics. This dual process emphasizes how biosecurity measures mediate species mobility, reflecting geopolitical priorities while challenging conventional notions of sovereignty in the Korean DMZ. By framing inter-Korean politics within the context of interspecies dynamics, this paper challenges the conventional view of the DMZ as a “pure” and “untouched” natural area. This study reframes the DMZ as a politically contested and ecologically dynamic space where interspecies relationships actively influence territorial practices and state sovereignty.